A Formal Approach to Service Specification and Matching based on Graph Transformation - Heckel, Reiko; Cherchago, Alexey; Lohmann, Marc (Proceedings of the First International Workshop on Web Services and Formal Methods (WSFM 2004), Pisa, Italy)

Systematic Validation of Model Transformations - Küster, Jochen (Proceedings 3rd UML Workshop in Software Model Engineering (WiSME 2004), Lisbon (Portugal))

Comparing two Model Transformation Approaches - Küster, Jochen; Sendall, Shane; Wahler, Michael (Proceedings of the Workshop on OCL and Model Driven Engineering (satellite event of the UML 2004), Lisbon (Portugal))

Towards Inconsistency Handling of Object-Oriented Behavioral Models - Küster, Jochen (International Workshop on Graph Transformation (GT-VMT 2004), Barcelona (Spain))

UML for FPGA Synthesis - Schattkowsky, Tim; Rettberg, Achim (Proceedings of the International Workshop on UML for SoC Design (UML-SOC 2004), San Diego, CA (USA))

Taming Model Round-Trip Engineering - Sendall, Shane; Küster, Jochen (Proceedings of Workshop on Best Practices for Model-Driven Software Development (satellite event of the 19th Annual ACM Conference on Object-Oriented Programming, Systems, Languages, and Applications (OOPSLA 2004)), Vancouver (Canada))

Virtual conference: a telecooperative learning environment - Kremer, H.-Hugo (Networked Learning 2004. A research based conference on e-learning in higher education and lifelong learning)

Organisation und didaktische Ausrichtung des "Praxissemesters" im Rahmen des Diplomstudiengangs Wirtschaftspädagogik an der Universität Konstanz - Deißinger, T.; Kremer, H.-Hugo (Theorie-Praxis-Verzahnung in der beruflichen und gymnsasialen Lehrerbildung. Das Praxissemester in Baden-Württemberg.)

Qualifizierungsnetzwerke - Lernumgebung für Lehrkräfte? - Kremer, H.-Hugo (Lernfelder gestalten - miteinander Lernen - Innovationen vernetzen. Ergebnisse der 1. CULIK Fachtagung (12.05.2004))

Virtual conference - a cooperative learning environment for teacher education? - Kremer, H.-Hugo (The annual conference of the Association for Information Technology in Teacher Education)

Qualifizierungsnetzwerke - Lernumgebung für Lehrkräfte - Kremer, H.-Hugo (Lernfelder gestalten - miteinander Lernen - Innovationen vernetzen. Ergebnisse der 1. CULIK Fachtagung)

Cross-layer optimization of OFDM transmission systems for MPEG-4 video streaming - Gross, James; Klaue, Jirka; Karl, Holger; Wolisz, Adam (Computer Communications)

Ambient networks: An architecture for communication networks beyond 3G - Niebert, Norbert; Schieder, Andreas; Abramowicz, Henrik; Malmgren, G.; Sachs, Joachim; Horn, Uwe; Prehofer, Christian; Karl, Holger (IEEE Wireless Communications)

Improving the Energy Efficiency of Directed Diffusion Using Passive Clustering - Handziski, Vlado; Köpke, Andreas; Karl, Holger; Frank, Christian; Drytkiewicz, Witold (Wireless Sensor Networks, First European Workshop, EWSN 2004, Berlin, Germany, January 19-21, 2004, Proceedings)

Research Challenges in Mobility and Moving Networks: An Ambient Networks View - Typpö, Ville; Eisl, Jochen; Höller, Jan; Agüero, Ramon; Karl, Holger (Broadband Satellite Comunication Systems and the Challenges of Mobility - IFIP TC6 Workshops on Broadband Satellite Communication Systems and Challenges of Mobility, World Computer Congress, August 22-27, 2004, Toulouse, France)

Consistency challenges of service discovery in mobile ad hoc networks - Frank, Christian; Karl, Holger (Proceedings of the 7th International Symposium on Modeling Analysis and Simulation of Wireless and Mobile Systems, MSWiM 2004, Venice, Italy, October 4-6, 2004)

A Geometric Derivation of the Probability of Finding a Relay in Multi-rate Networks - Marie Feeney, Laura; Hollos, Daniel; Kubisch, Martin; Mengesha, Seble; Karl, Holger (NETWORKING 2004, Networking Technologies, Services, and Protocols; Performance of Computer and Communication Networks; Mobile and Wireless Communication, Third International IFIP-TC6 Networking Conference, Athens, Greece, May 9-14, 2004, Proceedings)

Regionalizing global optimization algorithms to improve the operation of large ad hoc networks - Hollos, Daniel; Karl, Holger; Wolisz, Adam (2004 IEEE Wireless Communications and Networking Conference, WCNC 2004, Atlanta, Georgia, USA, 21-25 March 2004)

Queue-driven cut-through medium access in wireless ad hoc networks - Raguin, David; Kubisch, Martin; Karl, Holger; Wolisz, Adam (2004 IEEE Wireless Communications and Networking Conference , WCNC 2004, Atlanta, Georgia, USA, 21-25 March 2004)

Data Transmission in Mobile Communication Systems - Karl, Holger (Location-Based Services)

Wireless Sensor Networks

Coherent dynamics in InGaAs quantum dots and quantum dot molecules - Langbein, W.; Borri, P.; Woggon, U.; Schwab, M.; Bayer, M.; Fafard, S.; Wasilewski, Z.; Hawrylak, P.; Stavarache, V.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Magnetic field dependence of hole levels in InAs quantum dots - Reuter, Dirk; Kailuweit, P.; Wieck, A.D.; Zeitler, U.; Maan, J.C. (Physica E: Low-dimensional Systems and Nanostructures)

Preparation and characterization of epitaxial Fe(001) thin films on GaAs(001)-based LED for spin injection - Schuster, E.; Keune, W.; Lo, F.-Y.; Reuter, Dirk; Wieck, A.; Westerholt, K. (Superlattices and Microstructures)

Electroluminescence of single-dot nano-LEDs—optical spectroscopy of an electrically tunable few-electron/hole system - Schmidt, R.; Vitzethum, M.; Fix, R.; Scholz, U.; Malzer, S.; Metzner, C.; Kailuweit, P.; Reuter, Dirk; Wieck, A.; Hübner, M.C.; Stufler, S.; Zrenner, A.; et al. (Physica E: Low-dimensional Systems and Nanostructures)

Dual-gate GaAs/AlGaAs quantum point contact with tuneable subband energy separation - Kähler, D; Knop, M; Kunze, U; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

Ultrasmall nanoscale devices fabricated from compensating-layer GaAs/AlGaAs heterostructures - Kähler, Dirk; Kunze, Ulrich; Reuter, Dirk; D. Wieck, Andreas (Physica E: Low-dimensional Systems and Nanostructures)

The linearly graded two-dimensional p–n junction - Petrosyan, S.; Yesayan, A.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Laterally patterned high mobility two-dimensional electron gases obtained by overgrowth of focused ion beam implanted Al1−xGaxAs - Riedesel, C; Reuter, Dirk; Wieck, A.D (Physica E: Low-dimensional Systems and Nanostructures)

Frequency-dependent C(V) spectroscopy of the hole system in InAs quantum dots - Reuter, Dirk; Schafmeister, P.; Kailuweit, P.; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Fabrication of two-dimensional n- and p-type in-plane gate transistors from the same p-doped GaAs/In0.1Ga0.9As/Al0.33Ga0.67As heterostructure - Reuter, Dirk; Seekamp, A; Wieck, A.D (Physica E: Low-dimensional Systems and Nanostructures)

High frequency conductance of a quantum point contact - Regul, J.; Hohls, F.; Reuter, Dirk; Wieck, A.D.; Haug, R.J. (Physica E: Low-dimensional Systems and Nanostructures)

Fabrication of two-dimensional p–n junctions formed by compensation doping of p-modulation doped GaAs/InyGa1−yAs/AlxGa1−x As heterostructures - Reuter, Dirk; Werner, C.; Riedesel, C.; Wieck, A.D.; Schuster, D.; Hansen, W. (Physica E: Low-dimensional Systems and Nanostructures)

Self-assembled quantum dots as probes for Landau-level spectroscopy - Russ, M; Lorke, A; Reuter, Dirk; Schafmeister, P (Physica E: Low-dimensional Systems and Nanostructures)

Separately contacted edge states in the fractional quantum Hall regime - Würtz, A.; Deviatov, E.V.; Lorke, A.; Dolgopolov, V.T.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Control of fine-structure splitting and biexciton binding inInxGa1−xAsquantum dots by annealing - Langbein, W.; Borri, P.; Woggon, U.; Stavarache, V.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Magnetization of multi-component two-dimensional quantum-Hall systems - Schaapman, M.R.; Zeitler, U.; Christianen, P.C.M.; Maan, J.C.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Capacitance and tunneling spectroscopy of InAs quantum dots - Schmidt, K. H.; Bock, C.; Versen, M.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Journal of Applied Physics)

Hall magnetometry on Co, Fe, and Py nanowires - Reuter, Dirk; Hoch, S.; Hausmanns, B.; Stahlmecke, B.; Dumpich, G.; Wieser, R.; Nowak, U.; Wieck, A.D. (Journal of Magnetism and Magnetic Materials)

Radiatively limited dephasing in InAs quantum dots - Langbein, W.; Borri, P.; Woggon, U.; Stavarache, V.; Reuter, Dirk; Wieck, A. (Physical Review B)

Two relaxation mechanisms observed in transport between spin-split edge states at high imbalance - Deviatov, E. V.; Würtz, A.; Lorke, A.; Yu. Melnikov, M.; Dolgopolov, V. T.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Magnetotransport in C-doped AlGaAs heterostructures - Grbić, B.; Ellenberger, C.; Ihn, T.; Ensslin, K.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Magnetic-field-induced excitons in photoluminescence from heavily doped p-type Ga1−xAlxAs/GaAs single heterojunction - Bryja, L.; Kubisa, M.; Ryczko, K.; Misiewicz, J.; Stȩpniewski, R.; Byszewski, M.; Potemski, M.; Reuter, Dirk; Wieck, A. (Physica B: Condensed Matter)

In-plane gate transistors in AlxGa1−xN/GaN heterostructures written by focused ion beams - Ebbers, A.; Reuter, Dirk; Heuken, M.; Wieck, A.D. (Superlattices and Microstructures)

New Britain as Consumer Country and Commodity - Tönnies, Merle (Journal for the Study of British Cultures)

Wirtschaftspädagogische Sichtweise der Spannungsverhältnisse in der Lehrerbildung vor dem Hintergrund des Lernfeldansatzes unter Berücksichtigung des Komplementärprinzips - Beutner, Marc; Twardy, M (Aktuelle Aspekte in Schule und wissenschaftlichem Unterricht. Studien und Berichte des IWP)

Ein Determinantenmodell der Ausbildungsbereitschaft von Klein- und Mittelbetrieben – Basis für eine systematische Förderung der Berufsausbildung - Beutner, Marc (Zukunft der Berufsausbildung in Deutschland: Empirische Untersuchungen und Schlussfolgerungen. Berichte zur Beruflichen Bildung 273)

Mergenthal, S.: A Fast-Forward Version of England, 2003 - Tönnies, Merle (Anglia)

Ambient Networks--Research for Communication Networks Beyond 3G - Niebert, Norbert; Flinck, Hannu; Hancock, Robert; Karl, Holger; Prehofer, Christian (13th IST Mobile and Wireless Communications-Summit 2004)

Throughput study for a dynamic OFDM-FDMA system with inband signaling - Gross, James; Paoluzzi, Irene; Karl, Holger; Wolisz, Adam (Vehicular Technology Conference, 2004. VTC 2004-Spring. 2004 IEEE 59th)

A hybrid approach for location-based service discovery in vehicular ad hoc networks - Klimin, Nikolay; Enkelmann, Wilfried; Karl, Holger; Wolisz, Adam (Proc. of WIT)

Distributed allocation of time slots for real-time traffic in a wireless multi-hop network - Carlson, Emma; Karl, Holger; Wolisz, Adam; Prehofer, Christian (Proc. European Wireless)

Capacity increase of multi-hop cellular wlans exploiting data rate adaptation and frequency recycling - Mengesha, Seble; Karl, Holger; Wolisz, Adam (Proc. of MedHocNet 2004)

Evolutionary equilibrium in Tullock contests: spite and overdissipation - Hehenkamp, Burkhard; Leininger, W.; Possajennikov, A. (European Journal of Political Economy)

Adiabatically driven electron dynamics in a resonant photonic band gap: Optical switching of a Bragg periodic semiconductor - Schaarschmidt, Martin; Förstner, Jens; Knorr, Andreas; Prineas, John P.; Nielsen, Nils C.; Kuhl, Jürgen; Khitrova, Galina; Gibbs, Hyatt M.; Giessen, Harald; Koch, Stephan W. (Physical Review B)
The adiabatic driving of the resonant electron dynamics in a one-dimensional resonant photonic band gap is proposed as an optical mechanism for nonlinear ultrafast switching. Pulsed excitation inside the photonic gap results in an ultrafast suppression and recovery of the gap. This behavior results from the adiabatic carrier dynamics due to rapid radiative damping inside the band gap.
Keywords: tet_topic_qw

Polaron signatures in the line shape of semiconductor ;intersubband transitions: quantum kinetics of the electron–phonon interaction - Butscher, S.; Förstner, Jens; Waldmüller, I.; Knorr, A. (physica status solidi (b))
We present a theory of the optical line shape of coherent intersubband transitions in a semiconductor quantum well, considering non-Markovian LO-phonon scattering as major broadening mechanism. We show that a quantum kinetic approach leads to additional polaron resonances and a resonance enhancement for gap energies close to the phonon energy.
Keywords: tet_topic_qw

Linear and nonlinear pulse propagation in a multiple-quantum-well photonic crystal - Nielsen, N. C.; Kuhl, J.; Schaarschmidt, M.; Förstner, Jens; Knorr, A.; Koch, S. W.; Khitrova, G.; Gibbs, H. M.; Giessen, H. (Physical Review B)
We investigate the temporal and spectral properties of subpicosecond pulses transmitted on the heavy-hole exciton transition through a multiple-quantum-well Bragg structure, exhibiting a one-dimensional photonic band gap. At low light intensities, a temporal propagation beating is observed. This beating is strongly dependent on the optical dephasing time T2 which is dominated by the radiative interwell coupling. In an intermediate intensity regime, the Pauli-blocking nonlinearity leads to gradual suppression of the photonic band gap and vanishing of the linear propagation beating. For highly nonlinear excitation, we find signatures of selfinduced transmission due to Rabi flopping and adiabatic following of the carrier density. Numerical simulations using the semiconductor Maxwell-Bloch equations are in excellent agreement with the experimental data up to intensities for which higher many-particle correlations become more important and self-phase modulation occurs in the sample substrate.
Keywords: tet_topic_qw

Subpicosecond spatiotemporal pulse compression in a nonlinear defocusing material - Nielsen, Nils. C.; Siederdissen, Tilmann H. zu; Kuhl, Jürgen; Schaarschmidt, Martin; Förstner, Jens; Knorr, Andreas; Koch, Stephan W.; Giessen, Harald (International Conference on Ultrafast Phenomena 2004)
We demonstrate temporal and spatial pulse compression and modulational instabilities in the nonlinear defocusing regime near the band edge of bulk GaAs. Experiment and theory show that spatiotemporal coupling is responsible for these surprising phenomena.
Keywords: tet_topic_polariton

Temporal phase evolution during excitonic Rabi flopping in semiconductors - Höner zu Siederdissen, Tilman; Nielsen, Nils Christian.; Kuhl, Jürgen; Förstner, Jens; Knorr, Andreas; Giessen, Harald (International Quantum Electronics Conference and Photonic Applications Systems Technologies)
Theoretically and experimentally, we investigate temporal phase evolution during Rabi-flopping on the A-exciton resonance in CdSe using a novel fast-scanning XFROG method and observe phase changes smaller than π/2 compared to the slightly-chirped input pulse.
Keywords: tet_topic_qd

Temporal and spatial compression of near-resonant pulses in a nonlinear defocusing semiconductor - Nielsen, Nils C.; Kuhl, Jürgen; Schaarschmidt, Martin; Förstner, Jens; Knorr, Andreas; Koch, Stephan W.; Giessen, Harald (Conference on Lasers and Electro-Optics/International Quantum Electronics Conference and Photonic Applications Systems Technologies)
The coupled spatiotemporal characteristics of subpicosecond pulses propagating in the nonlinear defocusing regime near the band edge of bulk GaAs are investigated experimentally and theoretically. We demonstrate pulse compression both in time and transverse space.
Keywords: tet_topic_polariton

Nonlinear light pulse propagation in Bragg-periodic multiple semiconductor quantum well samples: ultrafast switching of a resonant photonic band gap - Schaarschmidt, Martin; Förstner, Jens; Knorr, Andreas; Prineas, John P.; Nielsen, Nils C.; Kuhl, Jürgen; Kithrova, Galina; Gibbs, Hyatt M.; Giessen, Harald; Koch, Stephan W. (Conference on Lasers and Electro-Optics/International Quantum Electronics Conference and Photonic Applications Systems Technologies)
We investigate theoretically the ultrafast nonlinear suppression of the resonant photonic band gap by strong laser pulses in semiconductor multiple qnantum wells. We achieve good agreement with our measurements on reflection samples.
Keywords: tet_topic_qw

Self-consistent Projection Operator Theory of Intersubband Absorbance in Semiconductor Quantum Wells - Waldmüller, Ines; Förstner, Jens; Knorr, Andreas (Nonequilibrium Physics at Short Time Scales)
Due to their many-particle character and their application in quantum cascade lasers, optical intersubband excitations in semiconductor quantum wells have become the focus of many recent publications [1,2]. In samples of high quality, intrinsic processes like electron-electron and electron-phonon many particle correlations determine the basic optical and transport properties such as lineshape and ultrafast dynamics. At the same time, intersubband excitations allow the direct investigation of dynamical properties of an important model system of many particle physics - the two-dimensional electron gas. We here present a microscopic theory for the intersubband dynamics and absorption. The calculation of absorption spectra of MQW systems is in principle composed of two parts: the determination of the polarization in a single quantum well within a density matrix approach as the source of electromagnetic radiation (Fig. 1a) and the calculation of the generated fields in the geometry of interest (Fig. 1b) within a Green's function approach [3,4]. We will here focus on the so-called single-pass geometry (cf. Fig. 1b, [5]).
Keywords: tet_topic_qw

Light Propagation and Many-Particle Effects in Semiconductor Nanostructures - Förstner, Jens
In dieser Arbeit wird eine Theorie vorgestellt, welche die quantenmechanische Vielteilchenphysik der Licht-Materie Wechselwirkung in Halbleiternanostrukturen beschreibt. Diese mikroskopische Beschreibung wird durch Kombination eines allgemeinen Dichtematrixansatzes mit speziellen Methoden zur Auswertung der Maxwellgleichungen wie der zeitaufgelösten Finite-Differenzen-Methode (FDTD) erreicht. Die Theorie wird auf verschiedene physikalische Situationen angewendet, wie z.B. Lichtausbreitung in Volumenhalbleitern, Interband- und Intersubbandübergänge in Quantenfilmstrukturen und optische Anregung von Quantenpunkten. Der Fokus liegt dabei auf der Beschreibung der linearen und nichtlinearen Antwort des Vielteilchensystems und seiner Ankopplung an das elektromagnetische Feld. In diesem Zusammenhang wird sowohl die Erzeugung als auch der Zerfall von optischen Anregungen untersucht, indem verschiedene Kopplungsmechanismen wie Elektron-Phonon-, Elektron-Photon- und Elektron-Elektron-Wechselwirkung berücksichtigt werden. Im Bereich der linearen Optik, also für Anregung mit geringer Intensität, ermöglicht die Theorie die Berechnung von Absorptionsspektren. Verschiedene Effekte in linearer Optik werden in dieser Arbeit untersucht und beschrieben: Linienaufspaltung durch Polaritonen im Volumenmaterial, Zunahme der Linienbreite bei Intersubbandübergängen verursacht durch Elektron-Elektron- und Elektron- Phonon-Streuung in einzelnen Quantenfilmen, Bildung einer optischen Bandlücke durch starke radiative Kopplung in Vielfilmstrukturen in Bragg-Geometrie, Phononenseitenbänder verursacht durch quantenkinetische Effekte in einzelnen Quantenpunkten und schliesslich Superradianz und Interferenzeffekte in Quantenpunktgittern. Bei nichtlinearer Anregung treten Dichte-Rabiflops als fundamentale Prozesse in allen betrachteten Systemen auf und können als kohärente Be- und Entvölkerung von quantenmechanischen Zuständen beobachtet werden. Der Einfluss von starker Lichtkopplung und verschiedenen Wechselwirkungen auf dynamische Größen wie die Besetzung wird untersucht. Bei nichtlinearer Propagation, bei der sich ein starker Lichtpuls über längere Strecken in einem System bewegt, wird selbstinduzierte Verstärkung der Transmission näher betrachtet. Des weiteren werden von der Coulombwechselwirkung verursachte nichtlineare Effekte wie exzitoninduziertes Dephasieren in Volumenmaterial und verschränkte Zustände in Quantenpunkten untersucht, die einen Zusammenbruch der Hartree-Fock- Näherung darstellen. Zusammenfassend werden in dieser Arbeit verschiedene lineare und nichtlineare optische Effekte in Halbleiternanostrukturen verschiedener Dimensionalität mit Hilfe einer allgemeinen Theorie, die einen Dichtematrixansatz mit den Maxwellschen Gleichungen kombiniert, untersucht.
Keywords: tet_topic_qd; tet_topic_qw; tet_topic_phc

Human Resource Management for International Joint Ventures: Expatriation and Selective Control - Kabst, Rüdiger (International Journal of Human Resource Management.)

Human Resource Management: The Need for Theory and Diversity - Weber, W; Kabst, Rüdiger (Management Revue: The International Review of Management Studies.)

Effektivität von Lösungsansätzen zur Bekämpfung von Spam - Schryen, Guido (Wirtschaftsinformatik)
Spam als unerwünschte Massen-E-Mail hat die Grenze von der Belästigung zur ökonomischen Relevanz längst überschritten. Ihr relativer Anteil am gesamten, weltweiten E-Mail-Aufkommen stieg in den vergangenen Jahren auf mehr als 50% im Jahr 2003. Es entstehen jährlich volkswirtschaftliche Schäden in Milliardenhöhe. Zur Bekämpfung des Spam-Problems werden neben gesetzlichen Regelungen vor allem technische Lösungen eingesetzt, bei denen das Blockieren und Filtern von E-Mails in praktisch eingesetzten Anti-Spam-Systemen dominieren. Dieser Artikel führt in die Spam-Problematik ein und beschreibt, bewertet und klassifiziert die derzeit bedeutendsten Verfahren zur Bekämpfung von Spam.
Keywords: Spam; E-Mail; Spoofing; Blockieren; Filtern; Lightweight Mail Transfer Agent Authentication Protocol (LMAP)

Fighting Spam: Motivating an Account-based Approach - Schryen, Guido (Proceedings of the IADIS International Conference WWW/Internet 2004. vol. 2)
Spam as unsolicited e-mail to a large number of recipients is known to ecome an increasingly disturbing and costly issue of electronic business and internet traffic. Mainly technical-oriented approaches are applied with a focus on blocking, filtering, and authentication mechanisms based on the domain name system. They come along with different drawbacks and have all low effectiveness in common. The article sketches these approaches, shows its limitations, and proposes an account-based approach where the number of e-mails per day and account is restricted.
Keywords: e-mail; spam; filtering; blocking; LMAP; SMTP account

How Security Problems Can Compromise Remote Internet Voting Systems - Schryen, Guido (Workshop of the ESF TED Programme)
Remote Internet voting systems still suffer from many security problems which rely on the clients, the servers, and the network connections. Denial-ofservice attacks and viruses still belong to the most challenging security issues. Projects and studies like the ?Voting Technology Project? of CALTECH and MIT or SERVE of the US Department of Defense set up to gain experience evidence many of the notional weaknesses of current Internet voting systems.

Neulich am Hotspot - Bringt Mobiles Internet die Menschen ins Netz? - Schryen, Guido (Digitale Teilung - digitale Integration : Perspektiven der Internetnutzung)

Das Praxissemester im Rahmen des Diplomstudiengangs Wirtschaftspädagogik an der Universität Konstanz - Organisation und didaktische Ausrichtung - Deißinger, T.; Kremer, H.-Hugo (Erziehungswissenschaft und Beruf)

Virtuelle Foren - Konsequenzen für Forschung und Entwicklung - Kremer, H.-Hugo (Studien zur Dynamik des Berufsbildungssystems. Forschungsbeiträge zur Struktur-, Organisations- und Curriculumentwicklung)

Complex teaching-learning arrangements and multimedia - Kremer, H.-Hugo (New Approaches to Vocational Education in Europe)

Focus groups as an instrument to implement innovations in VET - concepts and experience - Kremer, H.-Hugo (New Approaches to Vocational Education in Europe)

Wissen managen mit virtuellen Foren - eine (neue) Chance für Lernortkooperationen. Erfahrungen aus dem Modellversuch WISLOK - Kremer, H.-Hugo (Lernortkooperation und Bildungsnetzwerke 13. Hochschultage Berufliche Bildung 2004-BerufsBildung in der globalen NetzWerkGesellschaft)

Entwicklung und Implementation von Wissensforen zur Förderung von Netzwerken in der dualen Ausbildung - Kremer, H.-Hugo (Implementation und Verstetigung von Netzwerken in der beruflichen Bildung)

Bildungsmesse als Instrument der Berufswahlvorbereitung - Entwicklung und Implementation einer komplexen Lernumgebung - Kremer, H.-Hugo (Erziehungswissenschaft und Beruf)

Optical dephasing of coherent intersubband transitions in a quasi-two-dimensional electron gas - Waldmüller, I.; Förstner, Jens; Lee, S.-C.; Knorr, A.; Woerner, M.; Reimann, K.; Kaindl, R. A.; Elsaesser, T.; Hey, R.; Ploog, K. H. (Physical Review B)

Labeling Smart Dust - Bansal, Vikas; Meyer auf der Heide, Friedhelm; Sohler, Christian (12th Annual European Symposium on Algorithms (ESA 2004))
Given n distinct points p1, p2, ... , pn in the plane, the map labeling problem with four squares is to place n axis-parallel equi-sized squares Q1, ... ,Qn of maximum possible size such that pi is a corner of Qi and no two squares overlap. This problem is NP-hard and no algorithm with approximation ratio better than 1/2 exists unless P = NP [10]. In this paper, we consider a scenario where we want to visualize the information gathered by smart dust, i.e. by a large set of simple devices, each consisting of a sensor and a sender that can gather sensor data and send it to a central station. Our task is to label (the positions of) these sensors in a way described by the labeling problem above. Since these devices are not positioned accurately (for example, they might be dropped from an airplane), this gives rise to consider the map labeling problem under the assumption, that the positions of the points are not fixed precisely, but perturbed by random noise. In other words, we consider the smoothed complexity of the map labeling problem. We present an algorithm that, under such an assumption and Gaussian random noise with sufficiently large variance, has linear smoothed complexity.

Fighting against two adversaries - Bienkowski, Marcin; Korzeniowski, Miroslaw; Meyer auf der Heide, Friedhelm (Proceedings of the sixteenth annual ACM symposium on Parallelism in algorithms and architectures - SPAA '04)

Congestion, Dilation, and Energy in Radio Networks - Meyer auf der Heide, Friedhelm; Schindelhauer, Christian; Volbert, Klaus; Grünewald, Matthias (Theory of Computing Systems)

Scheduling against an adversarial network - Leonardi, S.; Marchetti-Spaccamela, A.; Meyer auf der Heide, Friedhelm (SPAA '04: Proceedings of the sixteenth annual ACM symposium on Parallelism in algorithms and architectures)

Global optimization of silicon nanoclusters - Chaudhuri, I.; Sertl, S.; Hajnal, Z.; Dellnitz, M.; Frauenheim, Th. (Applied Surface Science)

New spectral lower bounds on the bisection width of graphs - Bezrukov, S.; Elsässer, R.; Monien, B.; Preis, R.; Tillich, J.-P. (Theoretical Computer Science)

A Rigorous Numerical Method for the Global Analysis of Infinite-Dimensional Discrete Dynamical Systems - Day, S.; Junge, O.; Mischaikow, K. (SIAM Journal on Applied Dynamical Systems)

Optimal Diffusion Schemes and Load Balancing on Product Graphs - Elsässer, Robert; Monien, Burkhard; Preis, Robert; Frommer, Andreas (Parallel Processing Letters)
We discuss nearest neighbor load balancing schemes on processor networks which are represented by a cartesian product of graphs and present a new optimal diffusion scheme for general graphs. In the first part of the paper, we introduce the Alternating-Direction load balancing scheme, which reduces the number of load balance iterations by a factor of 2 for cartesian products of graphs. The resulting flow is theoretically analyzed and can be very high for certain cases. Therefore, we further present the Mixed-Direction scheme which needs the same number of iterations but computes in most cases a much smaller flow. In the second part of the paper, we present a simple optimal diffusion scheme for general graphs, calculating a balancing flow which is minimal in the l 2 norm. It is based on the spectra of the graph representing the network and needs only m-1 iterations to balance the load with m being the number of distinct eigenvalues. Known optimal diffusion schemes have the same performance, however the optimal scheme presented in this paper can be implemented in a very simple manner. The number of iterations of optimal diffusion schemes is independent of the load scenario and, thus, they are practical for networks which represent graphs with known spectra. Finally, our experiments exhibit that the new optimal scheme can successfully be combined with the Alternating-Direction and Mixed-Direction schemes for efficient load balancing on product graphs.

A set oriented approach to global optimal control - Junge, Oliver; Osinga, Hinke M. (ESAIM: Control, Optimisation and Calculus of Variations)

Uncertainty in the dynamics of conservative maps - Junge, O.; Marsden, J.E.; Mezic, I. (2004 43rd IEEE Conference on Decision and Control (CDC) (IEEE Cat. No.04CH37601))

openVisaar: Enriching Cooperative Visualization by Combining Open Technologies - Goetz, Frank; Domik, Gitta (Cooperative Design, Visualization, and Engineering, First International Conference, (CDVE) 2004, Palma de Mallorca, Spain, September 19-22, 2004, Proceedings)

An XML-based visual shading language for vertex and fragment shaders - Goetz, Frank; Borau, Ralf; Domik, Gitta (Proceeding of the Ninth International Conference on 3D Web Technology, Web3D 2004, Monterey, California, USA, April 5-8, 2004)

Operating systems for reconfigurable embedded platforms: online scheduling of real-time tasks - Steiger, Christoph; Walder, Herbert; Platzner, Marco (IEEE Transactions on Computers)

Multipath-Resistant Time of Arrival Estimation for Satellite Positioning - Bischoff, R.; Haeb-Umbach, Reinhold; Nammi, Sai Ramesh (AEUe, Int. Journal on Electronics and Communications)
Satellite positioning systems, such as GPS or the future European system Galileo, employ direct-sequence spread-spectrum signals. The positioning accuracy is strongly affected by the quality of the pseudo range measurements. These measurements necessitate code and carrier synchronization of the received signal with the internally generated reference signals. In this type of systems one major error source is the multipath phenomenon, which results in a sum of delayed and weighted copies of the original signal to be present at the receiver input. This can result in a systematic error of the code tracking loop resulting in range errors in the order of several tens of meters. In this paper we propose an extension of the standard code tracking loop capable of estimating the parameters of the line-of-sight (LOS) signal and separating the LOS from the reflected signal portions. It is based on an analysis of the cross correlation of the received signal with a locally generated code sequence in the vicinity of the tracking point of a Delay-Locked Loop (DLL). For this reason, we call this method Cross Correlation Function (CCF) Analysis. The proposed method achieves considerably more accurate estimates than a DLL. Its performance is comparable to the Multipath Estimating Delay-Locked Loop (MEDLL) which is considered to be the best method for reducing multipath induced errors, so far. However, the computational complexity of the CCF Analysis is by a factor of three smaller compared to the MEDLL. Extensive simulations have been conducted for the proposed method and the MEDLL in order to assess the robustness of the two approaches under various signal constellations.

Soft Features for Improved Distributed Speech Recognition over Wireless Networks - Haeb-Umbach, Reinhold; Ion, Valentin (International Conference on Spoken Language Processing (ICSLP 2004))
A major drawback of distributed versus terminal-based speech recognition is the fact that transmission errors can lead to degraded recognition performance. In this paper we employ soft features to mitigate the effect of bit errors on wireless transmission links: At the receiver a posteriori probabilities of the transmitted feature vectors are computed by combining bit reliability information provided by the channel decoder and a priori knowledge about residual redundancy in the feature vectors. While the first-order moment of the a posteriori probability function is the MMSE estimate, the second-order moment is a measure of the uncertainty in the reconstructed features. We conducted realistic simulations of GSM transmission and achieved significant improvements in word accuracy compared to the error mitigation strategy described in the ETSI standard.

Robust speaker direction estimation with particle filtering - Warsitz, Ernst; Haeb-Umbach, Reinhold (IEEE Workshop on Multimedia Signal Processing (MMSP 2004))
The paper is concerned with binaural signal processing for a bimodal human-robot interface with hearing and vision. The two microphone signals are processed to obtain an enhanced single-channel input signal for the subsequent speech recognizer and to localize the acoustic source, an important information for establishing a natural human-robot communication. We utilize a robust adaptive algorithm for filter-and-sum beamforming (FSB) and extract speaker direction information from the resulting FIR filter coefficients. Further, particle filtering is applied which conducts a nonlinear Bayesian tracking of speaker movement. Good location accuracy can be achieved even in highly reverberant environments. The results obtained outperform the conventional generalized cross correlation (GCC) method.
Keywords: bimodal human-robot interface; binaural signal processing; enhanced single-channel input signal; filter-and-sum beamforming; filtering theory; FIR filter coefficient; generalized cross correlation method; microphones; microphone signal; nonlinear Bayesian tracking; particle filtering; robust adaptive algorithm; robust speaker direction estimation; signal processing; speech enhancement; speech recognition; speech recognizer; user interfaces

Adaptive Beamforming Combined with Particle Filtering for Acoustic Source Localization - Warsitz, Ernst; Haeb-Umbach, Reinhold; Peschke, Sven (International Conference on Spoken Language Processing (ICSLP 2004))
While the main objective of adaptive Filter-and-Sum beamforming is to obtain an enhanced speech signal for subsequent processing like speech recognition, we show how speaker localization information can be derived from the filter coefficients. To increase localization accuracy, speaker tracking is performed by non-linear Bayesian state estimation, which is realized by sequential Monte Carlo methods. Improved acquisition and tracking performance was achieved even in highly reverberant environments, in comparison with both a Kalman Filter and a recently proposed Particle Filter operating on the output of a nonadaptive Delay-and-Sum beamformer.

Berufskollegs als Kompetenzzentren und die damit verbundenen Kooperationsanforderungen zwischen Bildungsgängen - Beutner, Marc; Twardy, M (Mensch. Bildung. Beruf. Herausforderungen an die Berufspädagogik. Dortmunder Beiträge zur Pädagogik)

Neue Methoden der Signalauswertung für Ultraschall-Messsysteme - Gulsch, Michael; Henning, Bernd
In der industriellen Messtechnik werden optische, chemische und akustische Messverfahren zur Ermittlung von Prozessgrößen eingesetzt. Dabei haben die akustischen Messverfahren aufgrund ihrer Robustheit und Wartungsfreundlichkeit ein sehr großes Einsatzgebiet. Impulsbasierte Ultraschallmesssysteme werden unter anderem zur Messung von Durchfluss und Füllstand eingesetzt. Zunehmend werden sie aber auch in der Flüssigkeitsanalytik zur Konzentrationsmessung und Stoffanalyse herangezogen. Dabei führen Gasblasen in den zu untersuchenden flüssigen Medien immer wieder zu Problemen, da bei Anwesenheit von Gasblasen die akustischen Stoffkenngrößen verändert werden. Diese Probleme können ihre Ursache auch in der Signalverarbeitung haben. Dieser Beitrag soll zeigen, welche Methoden zur Signalverarbeitung geeignet sind um dieses Problem zu lösen.

1/f-Frequency Fluctations and Phase Noise in MEMS Resonators - Handel, Peter; Henning, Bernd
The classical forms of noise present in the frequency of MEMS resonators have been recently investigated and described in detail. The present paper extends this investigation to 1/f noise. That is of fundamental nature in microelectromechanical systems (MEMS) resonators, and is given by the universal quantum 1/f effect. In recent years new piezoelectric and compound semiconductor materials have been developed along with advanced manufacturing technologies for MEMS including them. These technologies enable the deposition of thin compound semiconductor, or PZT films and their integration into MEMS devices.

Die akustische Impedanz als Messgröße zur Charakterisierung flüssiger Stoffsysteme - Henning, Bernd (Technisches Messen)

A Space Optimization Method for Time-Reversal Super-Focusing - Rautenberg, Jens; Olszewski, Dirk; Henning, Bernd (Proceedings of the Joint Congress CFA/DAGA 2004)
The appliance of time-reversal acoustics to classical trans-ducer design, medical, technical or audible range applica-tions brings forward new ideas whenever we need both, focusing acoustical energy in time and space. Unfortunately, the spatiotemporal focusing is limited through the amount of applied transducer elements as well as the ergodicity and randomness of the cavity [1]. This paper will show how the simulated annealing technique, a multi-objec¬tive optimiza-tion algorithm [2], is used to increase the nar¬rowness of the refocused spot by breaking up randomness for the benefit of ergodicity in a predetermined cavity.

A systematic approach to the assessment of fuzzy association rules - Dubois, D.; Hüllermeier, Eyke; Prade, H. (In Proceedings of the Workshop on Alternative Techniques for Data Mining and Knowledge Discovery, IEEE International Conference on Data Mining, Brighton, UK)